No relevant association between coronary artery ectasia and mean platelet volume, gamma-glutamyltransferase and uric acid levels - Bahadır Şarlı; Ahmet Oğuz Baktır; Hayrettin Sağlam; Hüseyin Arınç; Serkan Kurtul; Zakir Karadağ; Hüseyin Katlandur; Mahmut Akpek; Mehmet Güngör Kaya (KARE Publishing, 2013)
Objectives: In this study, we aimed to investigate whether there is an association between mean platelet volume (MPV), gamma-glutamyltransferase (GGT) and uric acid and coronary artery ectasia (CAE) in a large patient population. Study design: A total of 406 patients (245 male, 161 female; mean age: 55+-9 years) were selected retrospectively as the study population from among 3265 individuals who underwent coronary angiography between August 2011 and December 2012. Information regarding blood tests of the patients obtained during hospitalization was extracted from the institute electronic database. Results: MPV, GGT and uric acid levels were significantly higher in subjects with stenotic coronary artery disease (CAD) and in subjects with both CAD and CAE compared with subjects with isolated CAE and subjects with normal coronary arteries (NCA). There were no significant differences between the isolated CAE and NCA groups in terms of MPV (8.6+-1.2 fL vs. 8.6+-1.1, respectively, p=0.993), serum GGT (33+-15 U/L vs. 30+-15 U/L, respectively, p=0.723) and uric acid levels (5.4+-1.6 mg/dl vs. 5.2+-1.7 mg/dl, respectively, p=0.845). Conclusion: Unlike previous studies, our study failed to demonstrate any association between CAE and MPV, uric acid and GGT levels.